2021
DOI: 10.1002/ima.22549
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐level dilated convolutional neural network for brain tumour segmentation and multi‐view‐based radiomics for overall survival prediction

Abstract: Glioblastoma (GBM) is the most high-risk and grievous tumour in the brain that causes the death of more than 50% of the patients within one to 2 years after diagnosis. Accurate detection and prognosis of this disease are critical to provide essential guidelines for treatment planning. This study proposed using a deep learning-based network for the GBM segmentation and radiomic features for the patient's overall survival (OS) time prediction. The segmentation model used in this study was a modified U-Net-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…For the performance evaluation of the segmentation model, four metrics named DSC, sensitivity, specificity, and the HD are used. 7 It can be seen that this study has outperformed the existing techniques 10,16,17,30,34,48 for brain tumor segmentation. By analyzing the BraTS2019 and BraTS2020 datasets, the BraTS2020 dataset outperformed due to its larger training set.…”
Section: Segmentation Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…For the performance evaluation of the segmentation model, four metrics named DSC, sensitivity, specificity, and the HD are used. 7 It can be seen that this study has outperformed the existing techniques 10,16,17,30,34,48 for brain tumor segmentation. By analyzing the BraTS2019 and BraTS2020 datasets, the BraTS2020 dataset outperformed due to its larger training set.…”
Section: Segmentation Resultsmentioning
confidence: 72%
“…This study used five MLDC blocks for tumor segmentation with different dilation rates, shown in Figure 2. MLDCNN-123, MLDCNN-135, MLDC-357, MLDC-246, and MLDC-468 are implemented by setting the dilation rates of (1, 2, 3); (1,3,5); (3,5,7); (2,4,6); and (4,6,8), respectively, at each level of MLDC block. In the MLDCNN model, standard convolution is replaced with the 3D dilated convolution.…”
Section: Brain Tumor Segmentationmentioning
confidence: 99%
See 3 more Smart Citations